Managing crime for urban wellbeing and sustainable housing delivery: through the lens of residents and housing developers in Malaysia - Hew, William Wee-Lim; Lau, Siok Hwa; Goh, Gerald Guan-Gan; Low, Boon-Yee (Penerbit Universiti Kebangsaan Malaysia, 2019)
Social sustainability is a form of development that promotes a harmonious society that is conducive to residential integration and improvement of the population's quality of life. The rapid urbanization of today’s society has increased the costs of living and created much social problems and crime. Crime has turned new residential projects into urban ghettoes, driving property prices down, encouraging urban flight. The desertion of traditional housing estates and the poor sales performance of new residential projects has put a dampener into the national property market. Thus, this study was conducted in two stages at the southern region of Malaysia. First, semi-structured interviews were conducted with 24 residents in crime-prone localities using snowball sampling. Second, discussions were held with 11 housing developers. This paper discusses the impacts of crime on residents, the housing market, and how the issue may be resolved from the perspectives of these two groups of respondents. The interviews revealed the destabilizing nature of crime on the sustainability of urban housing and the gradual failing of traditional open neighbourhoods in favour of safer, gated and guarded neighbourhoods; it also revealed the difficult operational positions faced by property developers in the past in particular the high costs incurred and the large overhang units. This paper contributes by recommending how developers may incorporate crime-prevention measures through innovative spatial management practices such as in eco-housing to increase attractiveness of their projects while minimizing costs.